English Department Students' Ability in Constructing Restrictive and Nonrestrictive Adjective Clauses - Afdal Ade Hendrayana; Amri Isyam; Fitrawati Fitrawati (Universitas Negeri Padang, 2012)
The purposes of this study were to (1) describe the third year in academic year 2009/2010 in English Department student’s ability in constructing restrictive and nonrestrictive adjective clauses, (2) analyze what deviations are made by the students in constructing restrictive and nonrestrictive adjective clauses. The data of this study were grammar test that consisted of 38 questions; 19 questions for restrictive adjective clauses and 19 questions for nonrestrictive adjective clauses. Data were collected by using cluster sampling technique. The sample of this study was KP 1 class that consisted of 31 students. The findings of the study showed that the students’ ability in constructing restrictive adjective clauses was average (61.67%) and in constructing nonrestrictive adjective clauses was very poor (30.3%). Abstrak Tujuan penelitian ini adalah (1) mendiskripsikan kemampuan grammar mahasiswa tingkat III Jurusan Bahasa dan Sastra Inggris tahun masuk 2009/2010 dalam membuat restrictive dan nonrestrictive adjective clauses, (2) menganalisis kesalahan yang mereka lakukan dalam menggunakan restrictive dan nonrestrictive adjective clauses. Data penelitian ini menggunakan tes grammar yang berjumlah 38 soal; 19 soal untuk restrictive adjective clauses dan 19 soal untuk nonrestrictive adjective clauses. Data dikumpulkan dengan menggunakan teknik cluster sampling. Sampel penelitian adalah mahasiswa KP 1 berjumlah 31 orang. Temuan penelitian yaitu kemampuan grammar mahasiswa dalam membuat kalimat restrictive adjective clauses adalah sedang (61.67%) dan untuk nonrestrictive adjective clauses adalah sangat lemah (30.3%).